Late-Onset Psychosis in a Patient with Essential Thrombocythemia: A Case Report - Pasa, Laura Fogaça; Kist, Elisa Hartmann; Piffero, Guilherme Mombach; Bueno, Júlia; Medeiros, Pablo Merlo; Hofmeister, Carla Favero (Brazilian Journal of Case Reports, 2026)
Essential thrombocythemia (ET) is a chronic myeloproliferative neoplasm associated with thrombotic and neurological complications, whereas psychotic manifestations are uncommon. We report the case of a 40-year-old man with previously diagnosed ET who developed progressive late-onset psychotic symptoms after hydroxyurea discontinuation, including auditory and cenesthetic hallucinations, religious delusions, social withdrawal, and functional decline. Extensive investigation for secondary causes was performed. Cerebrospinal fluid analysis was unremarkable, and contrast-enhanced brain magnetic resonance imaging showed nonspecific white matter hyperintensities without acute ischemic lesions. Infectious, inflammatory, metabolic, and autoimmune etiologies were excluded. During hospitalization, olanzapine led to partial improvement of positive symptoms, although residual negative symptoms persisted during early follow-up. The coexistence of a hematological disorder associated with possible microvascular dysfunction and the absence of biomarkers of organic psychosis created diagnostic uncertainty between psychosis secondary to a medical condition and a primary schizophrenia-spectrum disorder. This case highlights the importance of comprehensive investigation and the challenges involved in distinguishing primary from secondary psychosis in patients with systemic diseases and atypical psychiatric presentations.